2023
DOI: 10.3389/fncel.2023.1166199
|View full text |Cite
|
Sign up to set email alerts
|

Early Draper-mediated glial refinement of neuropil architecture and synapse number in the Drosophila antennal lobe

Darren A. Jindal,
Hans C. Leier,
Gabriela Salazar
et al.

Abstract: Glial phagocytic activity refines connectivity, though molecular mechanisms regulating this exquisitely sensitive process are incompletely defined. We developed the Drosophila antennal lobe as a model for identifying molecular mechanisms underlying glial refinement of neural circuits in the absence of injury. Antennal lobe organization is stereotyped and characterized by individual glomeruli comprised of unique olfactory receptor neuronal (ORN) populations. The antennal lobe interacts extensively with two glia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 79 publications
2
12
0
Order By: Relevance
“…Brp is the Drosophila homolog of mammalian ELKS/CAST/ERC and is a structural component of the presynaptic electrondense T-bar (Wagh et al, 2006). We previously demonstrated that active zone size and presynapse number are indistinguishable when quantified by masking endogenous Brp signal or by driving cell type-specific overexpression of Brp-short (Jindal et al, 2023), validating our approach. We focused on defining the lowest odorant concentration leading to robust reductions in VM7 OSN innervation volume and presynaptic number.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Brp is the Drosophila homolog of mammalian ELKS/CAST/ERC and is a structural component of the presynaptic electrondense T-bar (Wagh et al, 2006). We previously demonstrated that active zone size and presynapse number are indistinguishable when quantified by masking endogenous Brp signal or by driving cell type-specific overexpression of Brp-short (Jindal et al, 2023), validating our approach. We focused on defining the lowest odorant concentration leading to robust reductions in VM7 OSN innervation volume and presynaptic number.…”
Section: Resultssupporting
confidence: 69%
“…While the response of AL glia to OSN axon injury has been thoroughly investigated (Herrmann et al, 2022;Logan et al, 2012;Ziegenfuss et al, 2012), glial roles in synapse formation, maintenance, and pruning in the AL are less clear. We previously investigated the function of the highly conserved glial engulfment receptor Draper in regulating axon terminal morphology and synapse number of several OSN populations across early and mid-adulthood to test for a role for Draper in shaping circuitry at baseline (Jindal et al, 2023). Intriguingly, the phenotypic and cell-type-specific consequences of losing glial Draper are not constant over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the EB-responsive VM7 glomerulus has been tested so far, and studies are needed for other odorant-selective glomeruli to determine the generalization of this mechanism. Glia subclasses differentially refine OSN synaptic architecture in a Draper-dependent mechanism 15 . Three glial classes function as phagocytes and can act cooperatively for neuronal phagocytosis in Drosophila juvenile brains 47 , 75 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, ethyl butyrate (EB)-responsive Or42a receptor olfactory sensory neurons (OSNs) innervating ventral medial 7 (VM7) glomeruli show extensive synaptic pruning in response to EB experience only during this short, defined critical period 10 , 11 . Importantly, glial cells can function as brain phagocytes to mediate experience-dependent synaptic pruning 13 15 , and glial phagocytosis is the primary mechanism of neuronal remodeling in Drosophila injury models and during early Drosophila brain development 16 18 .…”
Section: Introductionmentioning
confidence: 99%